ADAPTING TO UNCERTAINTY: BEHAVIORAL STRATEGIES OF INTERNATIONAL POLITICAL ACTORS - Kalashlinska, Maryna (Public Management and Policy, 2025)
This article examines the behavioral strategies employed by international political actors to adapt to conditions of profound uncertainty. The relevance of the topic lies in the growing need to revise theoretical and practical approaches in international relations, as classical rationalist models based on probabilistic reasoning are increasingly ineffective in the face of unpredictable challenges. The core analytical concerns identified in this study are the cognitive overload experienced by political leaders and the institutional inability of formal structures to respond adaptively. The aim of the paper is to identify and classify the key behavioral strategies used by international actors to navigate uncertainty. Methodologically, the research is grounded in conceptual analysis and the synthesis of insights from behavioral political theory and international political relations. Drawing on prospect theory and the bounded rationality model, the study reveals the psychological foundations of contemporary strategic behavior. The findings indicate a shift from long-term analytical planning to short-term, heuristic-based decision-making. Based on this, an original typology of behavioral adaptation strategies is proposed, which includes five core strategies: Strategic Hedging, Experimental Iteration, Narrative Dominance, Reflexive Entrenchment, and Strategic Shaping. This model enables a systematic analysis of political behavior through the lens of public policy outputs and cognitive constraints in decision-making. Its practical application can support the identification of strengths and weaknesses in state strategies and help set priorities for enhancing strategic resilience. The article concludes that in an era of systemic turbulence, the ability to psychologically adapt and maintain behavioral flexibility has become a more important source of international influence than the traditional material assets that shaped past power hierarchies. Future research should explore the influence of artificial intelligence on leaders’ cognitive processes and develop tools to strengthen the psychological resilience of governance systems.